Capitalism and evolution - Stan Metcalfe (The University of Manchester, Manchester Business School, 2011)
In this paper I pose an old fashioned question, "Why do capitalist economies evolve in the way that they do?" The answer will lie, on the one hand, in the nature of human curiosity and the corresponding growth of knowledge and, on the other hand, in the particular instituted rules of the game that induce the self transformation of each particular economic order. The essential idea is this; the manner of self transforming is contingent on the manner of self-ordering, so that different instituting frames have different dynamic consequences. Capitalist economies are also ignorance economies, in which highly specialised individuals and teams know a great deal about very little, so that the productive strength of the system, its collective knowing, depends on how the pools of specialised, narrow understandings are connected. Connectivity requires organisation and organisation depends on rules of the game and on belief and trust so that we can rely upon the testimony and actions of others. Failure of trust leads to failure of connectivity and a corresponding loss of system coherence. Order is central to the notion of economic evolution and, in practice, economic configurations demonstrate immense richness and subtlety but order is not equilibrium. Systems in equilibrium do not evolve. That the day to day structures of capitalism is the product of ordering processes seems to me self evident and it is equally self evident that these structures are restless, that their development is open-ended and unpredictable.
Keywords: G13; G17; 330